Peran Guru Agama Dalam Penanaman Islam Wasathiyah di Madrasah Aliyah Muhammadiyah 1 Malang - Hanist; Khozin (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
In the process of instilling Islam Washatiyah, it is necessary for Islamic Religious Education (PAI) teachers to provide deep understanding of religion to students and to be skilled in motivating them to apply it consciously in their lives. Although the role of Islamic teachers in instilling Islam Washatiyah is crucial, there are numerous challenges in its implementation. One of the challenges is the limited or incorrect understanding of Islam Washatiyah among some students. In some cases, religious teaching in schools still tends to be dogmatic and does not emphasize the values of Islam Washatiyah. Furthermore, external challenges, such as the influence of social media that often spreads extreme ideologies, worsen the situation, thus requiring specific strategies to instill the values of Islam Washatiyah in students. The purpose of this study is to describe and understand the role of PAI teachers in instilling the values of Islam Washatiyah in students at Madrasah Aliyah Muhammadiyah 1 in Malang City. This study uses a qualitative method with a field research design. The data collection methods used by the researcher include observation, interviews, and documentation. The results of this study indicate that the role of religious teachers in instilling Islam Washatiyah includes: first, the role as educators; second, the role as role models; third, the role as facilitators; and fourth, the role as evaluators.